THE APPLICATION OF LAW, GOING TO THE LAW ENFORCEMENT (AN ANALIZYNG OF THE RIIL SCIENTIFIC) - Faisol Azhari (Jurnal Pembaharuan Hukum, 2018)
Law or law order are not made to be observed and to be logical rational study only but to be done. Of course the application of law in society gets concretization proccess where the regulation of general and abstract normative law given for special, concrete and casuistic problems. It is not enough to implement limitted law on legal norms only normatively in societ, we have to observe more on social phenomena to implement the law flexibly. The implementation of law which is able to creat efective communication between the members of society, and not release from the final objective or the main goal of the legal politic namely to reach social welfare and protection as the integral part of the social policy, that is the implementation of law into the law enforcement.